ANALISIS DAMPAK PEMBANGUNAN SAMARINDA BARU (BSB) TERHADAP PROVINSI KALIMANTAN TIMUR - Nurqamarani, Adisty Shabrina; Reza, Faizal (RJABM (Research Journal of Accounting and Business Management), 2018)
This is a descriptive research regarding economic impact analysis of APT Pranoto Airport or called “Bandara Samarinda Baru” in East Kalimantan region. The aim of the project was to provide the evidence on the economic benefits resulted from Samarinda Baru airport by applying economic impact analysis. This article primarily focused on expenditure impacts as well as brief information of non-pecuniary impacts of Samarinda Baru airport project during operational phase. At the research stage, the project focused on examining the previous literatures of economic impact studies at the same time as investigating reports on the Samarinda Baru airport. The project involved a strong element of analysis on academic literatures, reports from Dinas Perhubungan Kalimantan Timur and Unit Pengelola Bandar Udara (UPBU) Kalimantan Timur. The methodology applied input output approach based on multipliers and relies on secondary data collection as primary method. The findings showed that there are numerous economic and non economic benefits resulted from the development of Bandara Samarinda Baru, included increase employment of local workers, increase expenditure within the region which impacted to better money circulation within the region, and also increase learning opportunities and create positive image towards cities around the airport location which in turn to economic welfare throughout East Kalimantan province. This finding can be used to emphasize Samarinda Baru airport contribution to East Kalimantan region and support its development in gaining funding and acceptance from local community.